2014
DOI: 10.2478/jlecol-2014-0016
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Parental Satisfaction of Children's Spaces Within High Rise Apartment Environments

Abstract: In the design process of open spaces within residential apartments, little attention is paid to children and their attitude to the environment is often ignored. Children, especially those who live in high-rise apartments, were found to have less connection with nature. Children supposedly need to engage in physical activities within outdoor areas, but urban planners, with the approval of managers or parents, must adequately design the open space for children. This paper initially reviews different research in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Moreover, a greater role of parents may be expected in preschool-aged children’s daily activity choices due to children’s early developmental stages [ 57 ]. However, parents of young children report less enjoyment with open areas than those without young children, according to a study [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a greater role of parents may be expected in preschool-aged children’s daily activity choices due to children’s early developmental stages [ 57 ]. However, parents of young children report less enjoyment with open areas than those without young children, according to a study [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nine researchers discussed the potential for UGSs to have positive impacts on releasing children's emotional pressures and increasing their living satisfaction. Eight papers discussed the role of UGSs in addressing emotional needs during the COVID-19 pandemic in urban areas, including promoting emotional development [58,64,65,80], releasing emotional stressors such as fear of sickness, spread of the virus, and concerns about pollution [55,56], lowering levels of behavioural and emotional problems [57], and offering emotional support [72,89]. Although children expressed fewer positive emotions during the COVID-19 pandemic, UGSs were considered to provide children with an avenue for reconnection [89].…”
Section: Sustaining Growth and Developmentmentioning
confidence: 99%
“…Eight papers discussed the role of UGSs in addressing emotional needs during the COVID-19 pandemic in urban areas, including promoting emotional development [58,64,65,80], releasing emotional stressors such as fear of sickness, spread of the virus, and concerns about pollution [55,56], lowering levels of behavioural and emotional problems [57], and offering emotional support [72,89]. Although children expressed fewer positive emotions during the COVID-19 pandemic, UGSs were considered to provide children with an avenue for reconnection [89]. Five studies concluded that having ample UGSs in neighbourhoods can increase children's satisfaction with life [70][71][72], including their perceived safety and satisfaction [24,70].…”
Section: Sustaining Growth and Developmentmentioning
confidence: 99%
See 2 more Smart Citations